Concept and Judgment in Brentano's Logic Lectures : Analysis and Materials - Rollinger, Robin D., (Studien zur Österreichischen Philosophie ;, 2021)
Concept and Judgment in Brentano's Logic Lectures is concerned with a crucial aspect of Brentano's philosophy as it was developed in his logic lectures from c. 1870 to c. 1885. The first part of the volume is an analysis of his theory of concept and judgment. The second part consists of materials, including a German edition and English translation of notes that a student took from a lecture course that Brentano gave. A short book by this student on Brentano is also translated in the materials. The access to Brentano's philosophy is enhanced by this volume not only with regard to his logic as a theory of deductive inference, but also to his descriptive psychology, metaphysics, and philosophy of language.